The Roles of Thai Politicians in a Thai Football Club: Business or Politics - sonphlay, chalinee (King Prajadhipok’s Institute Journal, 2020)
Nowadays there are several politicians and their relatives taking part in Thai football clubs. From 2011-2014, 12 out of 26 clubs in the Thai Premier League were owned or sponsored by politicians. This study tries to explain the increasing roles of Thai politicians in football clubs by focusing on economic structure and political context. The study revealed that there are five crucial conditions that enable and attract politicians to invest in football clubs. (1) The unification of Thai League (a league for clubs located in Bangkok) and Provincial League (a league for provincial clubs) into a single league as Thailand Premiere League caused Thai professional football competition to become more popular. (2) The decentralization under the 1997 Constitution made local politics more important and allowed local authorities to take responsibility for promoting local sport and managing sport stadiums. (3) The institutionalization of elections in Thai politics after the so-called semidemocracy era made election the only legitimate path to political office. It drove politicians to pay closer attention to their voters. Thus, the popularity of football is seen as one powerful means to building and maintaining the relationship between politicians and voters. (4) Currently, football clubs in Thailand are not economically profitable businesses. As a result, club ownership is not attractive to ordinary businessmen, but it is to politicians. Politicians have an advantaged economic status, compared with others within their localities, so they are able to sponsor and get non-economic benefits from a football club.